2015
DOI: 10.1016/j.cropro.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Meloidogyne javanica and its relationship with the leaf chlorophyll content in zucchini

Abstract: Root-knot nematodes (RKN), Meloidogyne spp., are major limiting factors for vegetable production worldwide (Sikora and Fernandez, 2005). Management of nematode problems in RKN conductive systems, such as protected cultivation in plastic greenhouses, is a major challenge since crop intensity and environmental conditions under the plastic cover favor pest and disease development. Crops with long and short cycles are cultivated generally in rotation with solanaceous (tomato, pepper and eggplants) and cucurbitaceo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Therefore, the only significant differences reported were in growth. In fact, in previous studies changes in yield of grafted and ungrafted cucumber were related to the relative variation in both chlorophyll refelctance and net photosynthetic rate [16], confirming previous results in which relative dry top weight of cucumber [17] or zucchini-squash biomass [18] was related to relative leaf chlorophyll content measured earlier in the plant-nematode interaction and in situations in which root-knot nematode was the main agent of biotic stress. Alternatively, the effect of nematodes in the plant status was mild but accumulative.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, the only significant differences reported were in growth. In fact, in previous studies changes in yield of grafted and ungrafted cucumber were related to the relative variation in both chlorophyll refelctance and net photosynthetic rate [16], confirming previous results in which relative dry top weight of cucumber [17] or zucchini-squash biomass [18] was related to relative leaf chlorophyll content measured earlier in the plant-nematode interaction and in situations in which root-knot nematode was the main agent of biotic stress. Alternatively, the effect of nematodes in the plant status was mild but accumulative.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, in agreement with previous studies, nematode infection caused a reduction in leaf chlorophyll content (Audebert et al 2000 ;Ahmed et al 2009 ;Khan and Haque 2011 ;Giné et al 2014 ;López-Gómez et al 2015 ) as well as in photosynthetic activity (Loveys and Bird 1973 ;Melakeberhan et al 1985 ) as suggested by the negative relationship between Pi and net photosynthetic rate. In addition, for both grafted or ungrafted cucumber plants, relative changes in yield were also related to the relative variation in both R / [R x R ] and net photosynthetic rate, confirming previous results in which relative dry top weight of cucumber or zucchinisquash biomass (López-Gómez et al 2015 ) was related to relative leaf chlorophyll content. These results suggest that reflectance based chlorophyll indices might provide an estimation of the effects of Pi on photosynthetic capacity and their effects, thereof, on yield in situations in which RKN is the main biotic stressful agent.…”
Section: Discussionsupporting
confidence: 78%
“…Those parameters refer to nematode population growth but do not provide valuable information on marketable crop yield, which is provided by the relationship between Pi and relative crop yield by the Seinhorst damage function model, the tolerance limit and the minimum relative yield (Seinhorst 1965 ). It is known that plant growth and yield are reduced at increasing Pi above the tolerance limit due to a reduction of water and nutrient intakes, and consequently, a reduction of plant conductivity and transpiration, as well as leaf chlorophyll content and photosynthesis rate (Loveys and Bird 1973 ;Melakeberhan 2003 to Pi (Melakeberhan et al 1985 ;Giné et al 2014 ;López-Gómez et al 2015 ). Therefore, these ecophysiological parameters might be potential indicators of tolerance and yield losses, but it needs to be evaluated under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Females reaching the egg‐laying stage showed reduced fecundity. This resistance has proven effective against several M. incognita isolates on a range of zucchini genotypes (López‐Gómez et al ., 2015b; Verdejo‐Lucas & Talavera, ). Intermediate resistance can be useful to regulate population increases, particularly in non‐chemical sustainable agriculture, because the genetic background of the plant may provide tolerance to nematode damage due to superior vigour, an extensive root system or tolerance to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%